Implementation of target costing in the Saudi Arabian food and beverages industry: the mediating role of supply chain management / Hussein Hussein Hamood Sharaf-Addin - Sharaf-Addin, Hussein Hussein Hamood (Universiti Teknologi MARA, 2021)
Target Costing (TC) has been widely recognized by many organizations worldwide, but the inclusion of Supply Chain Management (SCM) when implementing TC is ambiguous. This study examined the implementation of TC through the mediation role of SCM based on the company strategies employed in the Saudi Arabian food and beverage industry. A questionnaire link was posted to 248 companies that were selected from a total of 791 companies, in which 186 responses were received and used for this study. The results revealed that the suppliers’ participation had a significant mediating role in the relationship between price-based TC processes and TC financial and non-financial implications. Moreover, customers’ inputs displayed a significant mediating role in the relationship between value based TC processes and TC financial and non-financial implications. Interestingly, these effects were found to be different among companies adopting the confrontation strategy and those adopting non-confrontation strategies, namely cost leadership and differentiation. This study addressed the significant gap in the literature regarding the mediating role of SCM when implementing the TC technique. From a methodological perspective, this study provides a new method of analysis that combines the use of the Rasch Measurement Model (RMM) and Structural Equation Modeling (SEM) for management accounting research.